Dieta del pez chile lucio Synodus scituliceps (Aulopiformes: Synodontidae) en la Costa Este del Golfo de California, México - Rodríguez-Romero, Jesús; López-Martínez, Juana; Ochoa Díaz, Ma. Ruth; Herrera-Valdivia, Eloísa (Revista de Biología Marina y Oceanografía, 2020)
This study provides information on feeding habits of the lizardfish Synodus scituliceps, one of the most abundant and frequent species in shrimp by-catch in the demersal area in the eastern coast of the Gulf of California, Mexico. Stomach content analyses were performed on 114 organisms caught from August 2004 to March 2005, and Levin’s index was applied. The most important prey species were benthic fishes: Eucinostomus currani, Opisthonema libertate, Synodus lucioceps and Paralichthys californicus. According to the Levin’s index (Bi = 0.39), S. scituliceps is a piscivorous specialist predator in soft bottoms, with similar diet in juveniles and adults.